Implementation of a Dependable Multiprocessor CubeSat - Samson, John R (2011 Aerospace Conference, 2011)
Space applications have been, and will continue to be, subject to severe size, weight, and power constraints. The need for and the use of high performance embedded computing in space exacerbates the size, weight, and power problems. Flying high performance embedded computing in CubeSat applications presents particularly unique problems which require unique solutions. Fortunately, there are three technologies that make flying high performance embedded computing on CubeSats feasible: 1) the availability of high power CubeSats, 2) the availability of small, light-weight, low-power, Commercial-Off-The-Shelf (COTS) Computer-on-Module (COM), e.g., Gumstix™, technologies which are potential solutions to the size, weight, and power problems, and 3) platform-, technology-, and application-independent Dependable Multiprocessor Middleware (DMM), which allows COTS COM technologies to be used in space applications. The paper provides a brief overview of these three technologies and presents the results of investigations of DM CubeSat implementations to date.